Comparative SPR Analysis of Intermolecular Interactions Performed Using the Original Biacore CM5 Chip and its Analog CMD500M - Gnedenko, O.V.; Ershov, P.V.; Mezentsev, Y.V.; Kaluzhskiy, L.A.; Yablokov, E.O.; Gilep, A.A.; Ivanov, A.S. (Biomedical Chemistry: Research and Methods, 2024)
Currently, users of Biacore SPR biosensors (“Cytiva”, USA) are faced with sanctions restrictions on the purchase of consumables (primarily optical chips) for this type of equipments. In this regard, the use of commercially available analogues of the optical chips has become relevant. In this work, a comparative study of molecular interactions was performed on a Biacore X100 SPR biosensor using an original Biacore CM5 optical chip (“Cytiva”, USA) and its analogue CMD500M (“XanTec bioanalytics GmbH”, Germany). Protein A was immobilized on both chips as a molecular ligand, often used in scientific research and biotechnological works to immobilize antibodies on various carriers (biosensor chips, sorbents, nano- and microparticles). An IgG antibody was used as a protein analyte. A comparative study of the interaction of various concentrations of antibodies with protein A immobilized on two versions of the chips was carried out. The values of the kinetic rate constants for the association (kon) and dissociation (koff) of complexes, as well as the equilibrium dissociation constant (Kd), were calculated from the obtained sensorgrams using the interaction model 1:1 (Langmuir) binding. The results of comparative measurements showed similar values of the rate constants and interaction affinities. The differences between the values of kon, koff and Kd were 18%, 10% and 9%, respectively. Thus, this study confirmed the interchangeability of the original SPR chips CM5 and their analogues CMD500M.